1996
DOI: 10.1116/1.580307
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption and ionization of HCl on an ice surface

Abstract: In this article, we describe a series of experiments investigating the interaction of the important stratospheric reservoir species HCl with the surface of a thin ice film. Reflection absorption infrared spectroscopy and thermal desorption spectroscopy have been used to identify the nature of the ionic hydrates formed under a variety of pressure, temperature, and exposure regimes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
82
1

Year Published

1997
1997
2010
2010

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(98 citation statements)
references
References 20 publications
15
82
1
Order By: Relevance
“…30,31,34,35 This observation strongly suggests that solvation and ionization dominate the interaction of HCl and HBr with both crystalline and amorphous microporous ice films at 110 K:…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…30,31,34,35 This observation strongly suggests that solvation and ionization dominate the interaction of HCl and HBr with both crystalline and amorphous microporous ice films at 110 K:…”
Section: Discussionmentioning
confidence: 88%
“…The line positions observed are in good agreement with similar transmission and reflection absorption spectra in the literature. 30,31 No other absorptions were observable over the entire mid infrared range of our detector (4000-650 cm -1 ), suggesting our hydrogen halide samples were free from impurities that absorb in the mid infrared. Following vapor deposition of the hydrogen halides, the temperature was increased at a rate of 10 K min -1 and the hydrogen halide films rapidly desorbed.…”
Section: Resultsmentioning
confidence: 93%
“…6,39,40 Of particular relevance to this work is the observation that the hexahydrate phase, HCl͑H 2 O) 6 , has not been observed to nucleate from the solid, but rather the melt supercooled to ϳ170 K, 38,39 with an HCl vapor pressure barrier of 5ϫ10 Ϫ5 torr. 31 Considerable work in this area is concerned with the possible dissociation of HCl on the surface, and with respect to the state of work in 1992, when the quasiliquid state was first proposed, ab initio and molecular dynamics calculations confirmed that HCl ionic dissociation was thermodynamically possible. 41,42 Later it was predicted that liquid formation was not necessary to promote dissociation on the surface.…”
Section: Introductionmentioning
confidence: 89%
“…Other studies report that complete ionization is observed spectroscopically at higher temperatures. 31,49 In other experiments above ϳ100 K a temperature dependent state of ionization is reported by Cs ϩ ion scattering, 50 and complete dissociation is measured by secondary-ion-mass spectroscopy, 51 near-edge x-ray absorption fine structure, 52 and temperature programmed desorption mass spectroscopy 53 techniques. Uptake experiments under conditions relevant to the upper atmosphere have indicated a dissociated state of adsorbed HCl.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation